2013
DOI: 10.1155/2013/196014
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Epistemological Trends in Students’ Understanding of Science from the Perspective of Large-Scale Studies

Abstract: This paper highlights how results from large-scale studies can be used to understand students' knowledge of science. Several scholars express critique of today's PISA framework, especially with regard to the presentation of the results as national rankings, and suggest alternative and complementary methods. The present study has used PISA data to reveal hidden patterns in the results. The results show a general descending trend in items focusing on the nature of science and how new scientific knowledge is gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 17 publications
0
5
0
6
Order By: Relevance
“…The findings of this study in terms of English language challenges are in line with previous studies [6,15,28,30,73,81], since language barriers may inhibit the ability of international students to take an active learning role inside the classroom. Even through the findings of the survey showed that international students face language challenges upon their arrival to study in Malaysia and could overcome language challenges with the passage of time, this does not eliminate the negative effect of language challenges on gaining sustainable learning among international students, especially since weak English language skills do not help them to improve their knowledge and skills, which they need for their future careers [53].…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…The findings of this study in terms of English language challenges are in line with previous studies [6,15,28,30,73,81], since language barriers may inhibit the ability of international students to take an active learning role inside the classroom. Even through the findings of the survey showed that international students face language challenges upon their arrival to study in Malaysia and could overcome language challenges with the passage of time, this does not eliminate the negative effect of language challenges on gaining sustainable learning among international students, especially since weak English language skills do not help them to improve their knowledge and skills, which they need for their future careers [53].…”
Section: Discussionmentioning
confidence: 94%
“…Intercultural challenges have been investigated by different studies, which showed that such challenges have a negative effect on students' learning and academic achievements [6,59]. The negative effect of intercultural challenges might have a negative effect on international students' learning outcomes, which is related to gaining sustainable learning [7,53,54]. Therefore, it is hypothesized that: Hypothesis 1 (H1).…”
Section: A Intercultural Challengesmentioning
confidence: 99%
See 2 more Smart Citations
“…Estos ítems, utilizados adecuadamente pueden aportar valiosa información a la educación en ciencias, como en el caso de Suecia, Dinamarca y Finlandia, países que a partir de los datos empíricos de algunos de estos ítems categorizaron el conocimiento científico de sus estudiantes y realizaron, entre otras mejoras, cambios en sus currículos que les han permitido mejorar en la cultura científica y así también obtener mejores resultados (Jakobsson, Davidsson, Karlsson y Oskarsson 2013). Sin embargo, en el trabajo de éstos autores (Jakobsson, et al 2013) sólo presentan un par de ítems como ejemplos de sus consideraciones y los demás son resultados generales del conjunto de los ítems que, aunque muy importantes, no dejan ver la esencia de cada uno de ellos. La esencia de los ítems es considerada muy importante, según Angell, Kjaernsli y Lie (2000), quienes partiendo de un análisis cualitativo de las respuestas dadas por los estudiantes a los ítems TIMSS (Trends in International Mathematics and Science Study) de ciencias -otra de las pruebas internacionales a nivel de estudiantes de primaria-concluyen que además de conocer cuánto saben los estudiantes, dan información diagnóstica de lo que saben, llegando a comprender el pensamiento del estudiante sobre el mundo.…”
Section: Contribución De Los íTems Pisaunclassified